INTER-RELIGIOUS HARMONY: a Historical Overview - noor achmad (Pascasarjana Universitas Wahid hasyim Semarang, 2013)
This paper generally aimed to find out that Islam is love andpeace religion. By using a historical approach, the writer triedto investigate a number of facts showing Islam has promotedinterreligious harmony and has from its inception laid thefoundation of relationship between Islam and other religions. Itmeans that it is not only theoretically but also practically. Basedon historical facts which have been well-documented in SirahNabawiyah, the Prophet Muhammad (pbuh) became the firstperson who practiced and implemented the teachings ofreligious tolerance; respecting and helping others andconducting religious dialogue to create harmonious life inmulticultural country, Medina. In this paper, the writers alsotried to explore not only interreligious harmony in thebeginning of Islamic history, particularly in prophet-Abbasidera but also in Indonesian contemporary which has recentlybecome an object of talks and research.Keywords: social harmony, Jews, Christian, MedinaCharter, belief